2008
DOI: 10.3748/wjg.14.7321
|View full text |Cite
|
Sign up to set email alerts
|

Scutellaria barbate extract induces apoptosis of hepatoma H22 cells via the mitochondrial pathway involving caspase-3

Abstract: of cell cycle, the percentage of cells in S phase was significantly decreased, while the percentage of cells in G 1 phase was increased. Flow cytometry assay also showed that ESB had a positive effect on apoptosis. Typical apoptotic morphologies such as condensation and fragmentation of nuclei and blebbing membrane of apoptotic cells could be observed under transmission electron microscope and fluorescence microscope. To further investige the molecular mechanism behind ESB-induced apoptosis, ESB-treated cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
(68 reference statements)
0
43
0
Order By: Relevance
“…Previous studies have shown that the water and organic solvent extracts of BZL can significantly inhibit the growth of human tumors (Cha et al, 2004;Yin et al, 2004;Goh et al, 2005;Suh et al, 2007;Dai et al, 2008;Kim et al, 2008;Wong et al, 2009). However, limited works have been attempted to elucidate its active components Wu and Chen, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that the water and organic solvent extracts of BZL can significantly inhibit the growth of human tumors (Cha et al, 2004;Yin et al, 2004;Goh et al, 2005;Suh et al, 2007;Dai et al, 2008;Kim et al, 2008;Wong et al, 2009). However, limited works have been attempted to elucidate its active components Wu and Chen, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…13 One such herb, Scutellaria barbata, known colloquially as Ban Zhi Lian (BZL101), has been shown to have anticancer properties in hepatocarcinoma and leukemia. More specifically, BZL101 is able to induce G 1 cell cycle arrest followed by apoptosis of these cancers 14,15 with effective concentrations of 2 mg/mL and 1 mg/ mL, respectively. Aqueous extracts of BZL101 contain several active anticancer compounds, 16 which are able to block glycolysis and induce cell death in a number of cancer cell lines, 17 and is well tolerated by metastatic breast cancer patients.…”
Section: Bzl101 a Phytochemical Extract From Thementioning
confidence: 99%
“…colon cancer, lung cancer, hepatoma, and skin cancer (Yin et al, 2004;Goh et al, 2005;Suh et al, 2007;Dai et al, 2008). Furthermore, our previous research found that CE-SB have antitumor activities both in vitro and in vivo .…”
Section: Protective Effects Of Scutellaria Barbata Against Rat Liver mentioning
confidence: 95%